2015
DOI: 10.1631/jzus.a1400285
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and properties of cold drawing Cu-2.5% Fe-0.2% Cr and Cu-6% Fe alloys

Abstract: High strength and high conductivity Cu-based materials are key requirements in high-speed railway and high-field magnet systems. Cu-Fe alloys represent one of the most promising candidates due to the cheapness of Fe compared to Cu-Ag and Cu-Nb alloys. The high strength of Cu-Fe alloys primarily relies on the high density of the Cu/Fe phase interface, which is controlled by the co-deformation of the Cu matrix and Fe phase. In this study, our main attention was focused on the deformation behavior of the Fe phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…One of the key issues in the research of Cu-Fe composites is improvement of the morphology and distribution of the primary Fe phase. Several studies have reported a refined Fe grain size with the addition of micro-alloying elements such as Cr [16], Ni [17], Si [18], Co [19], and Ag [20]. This multi-alloying method can improve the strength of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…One of the key issues in the research of Cu-Fe composites is improvement of the morphology and distribution of the primary Fe phase. Several studies have reported a refined Fe grain size with the addition of micro-alloying elements such as Cr [16], Ni [17], Si [18], Co [19], and Ag [20]. This multi-alloying method can improve the strength of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have introduced multi-alloying in Cu–Fe alloys to accelerate the precipitation of Fe during the solidification process by addition of micro-alloy elements, thus inhibiting the dissolution of Fe atoms in the Cu matrix. Ag has been widely studied as a third component to lower the solid solubility of Fe in Cu, and improve the strength of the material without markedly worsening the conductivity [2,5,6,7,8]. Meanwhile, because Fe atoms diffuse relatively slowly from a supersaturated Cu solid solution at room temperature, intermediate heat treatment and final aging treatment are often used to promote precipitation of Fe atoms [9,10,11].…”
Section: Introductionmentioning
confidence: 99%